Binding Effects of Grasses in Soil Conservation - Morachan, Y.B.; Mariakulandai, A. (Journal of Soil and Water Conservation, 2022)
Soil erosion is one of the most serious problems facing India to-day. It is estimated that about 200 million acres representing 25 percent of total area of India is affected by -erosion. The Cho•beds of Punjab hills, the Kotar (ravine) lands of Central India, the numerous gullies found in the hilly regions, the sheet and rill erosion found in the Deccan black soils and the sand dunes of Rajasthan desert indicate the havoc created by erosion both by water and wind in India.